Pendampingan Penyusunan Javanese Dictionary Sebagai Media Pembelajaran bagi Organisasi Daerah Luar Jawa di Pondok Pesantren Sunan Drajat - Dymas Yulia Putri Kusumaningtyas; Siti Alfi Faridlotul Jannah; Thoybatul Mahbubah; Yunita Viva Firdaus; Ziyadatut Thoyyibah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Differences in communication or language used in the process of students communicating need to be adjusted so that misunderstandings in communicating can be minimized. At the Sunan Drajat Islamic Boarding School Alone in daily activities the majority language used by students is Javanese. However, of the thousands of existing students, there are still many who cannot or know the Javanese language due to the background of the students who come from various regions. So it is necessary to have learning media that can provide convenience for students in learning Javanese. This assistance activity in the preparation of a Javanese dictionary uses the ABCD (Asset Based Community Development) approach, which is an approach that aims to develop an asset owned by a group or community, from which then it becomes a way for existing changes to be made. This activity is expected to be able to later become a means in realizing the learning media. From this mentoring activity, it produces a dictionary that can be used by the Management of the Outer Java Region in supporting students' learning to apply the Javanese language in daily activities.